Activation of RAF-1 through Ras and Protein Kinase Cα Mediates 1α,25(OH)2-Vitamin D3 Regulation of the Mitogen-activated Protein Kinase Pathway in Muscle Cells - Buitrago, Claudia Graciela (2003)
We have previously shown that stimulation of proliferation of avian embryonic muscle cells (myoblasts) by 1α,25(OH)2-vitamin D3 (lα,25(OH)2D3) is mediated by activation of the mitogen-activated protein kinase (MAPK; ERK1/2). To understand how lα,25(OH)2D3 up-regulates the MAPK cascade, we have investigated whether the hormone acts upstream through stimulation of Raf-1 and the signaling mechanism by which this effect might take place. Treatment of chick myoblasts with lα,25(OH)2D3 (1 nM) caused a fast increase of Raf-1 serine phosphorylation (1- and 3-fold over basal at 1 and 2 min, respectively), indicating activation of Raf-1 by the hormone. These effects were abolished by preincubation of cells with a specific Ras inhibitor peptide that involves Ras in lα,25(OH)2D3 stimulation of Raf-1. lα,25(OH)2D3 rapidly induced tyrosine de-phosphorylation of Ras-GTPase-activating protein, suggesting that inhibition of Ras-GTP hydrolysis is part of the mechanism by which lα,25(OH)2D3 activates Ras in myoblasts. The protein kinase C (PKC) inhibitors calphostin C, bisindolylmaleimide I, and Ro 318220 blocked lα,25(OH)2D3-induced Raf-1 serine phosphorylation, revealing that hormone stimulation of Raf-1 also involves PKC. In addition, transfection of muscle cells with an antisense oligodeoxynucleotide against PKCα mRNA suppressed serine phosphorylation by lα,25(OH)2D3. The increase in MAPK activity and tyrosine phosphorylation caused by lα,25(OH)2D3 could be abolished by Ras inhibitor peptide, compound PD 98059, which prevents the activation of MEK by Raf-1, or incubation of cell lysates before lα,25(OH)2D3 exposure with an anti-Raf-1 antibody. In conclusion, these results demonstrate for the first time in a lα,25(OH)2D3 target cell that activation of Raf-1 via Ras and PKCα-dependent serine phosphorylation plays a central role in hormone stimulation of the MAPK-signaling pathway leading to muscle cell proliferation.